1942
DOI: 10.1017/s0016756800073891
|View full text |Cite
|
Sign up to set email alerts
|

On a New Palaeolithic Industry from the Norfolk Coast

Abstract: The Glacial deposits along the Norfolk and Suffolk coasts are important to geologists and archaeologists, as some of the formations here, even those which are later than the Cromer Forest Bed Series, are earlier than those of many other districts. Finds of Palaeolithic implements in this area have not so far been abundant, but an industry was recorded by us in 1938 (see Nature, 19th November, 1938, p. 912), and it is now possible to give greater details about its mode of occurrence. The geological dating of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1944
1944
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The presence of Chalk and limestone pebbles proves that the Hessle is not a decalcified chalky boulder clay, and it weathers in a different way from either the Lower or Upper Chalky Boulder Clays of East Anglia. It has been accepted by Boswell (1) and Solomon (2) as the product of the last glaciation in this area, and this was also mentioned in a paper by Moir and myself (1942, p. 211) (3). The relation of the Hessle to earlier boulder clays is seldom seen, but it appears to rest on a chalky clay south of Burnham Deepdale (4).…”
Section: On the Occurrence Of Hessle Boulder Clay At Happisburgh Normentioning
confidence: 87%
“…The presence of Chalk and limestone pebbles proves that the Hessle is not a decalcified chalky boulder clay, and it weathers in a different way from either the Lower or Upper Chalky Boulder Clays of East Anglia. It has been accepted by Boswell (1) and Solomon (2) as the product of the last glaciation in this area, and this was also mentioned in a paper by Moir and myself (1942, p. 211) (3). The relation of the Hessle to earlier boulder clays is seldom seen, but it appears to rest on a chalky clay south of Burnham Deepdale (4).…”
Section: On the Occurrence Of Hessle Boulder Clay At Happisburgh Normentioning
confidence: 87%
“…A series of sands, the Corton Beds of Baden-Powell and Reid Moir, 19 lies between the North Sea Drift and the Lowestoft Till. These sands contain a fauna of marine molluscs described by Baden-Powell 20 .…”
Section: Marine Horizonsmentioning
confidence: 99%
“…The Marly Drift was assigned to the Anglian (or its equivalent) Stage by Solomon (1932), Baden-Powell and Moir (1942) and Baden-Powell (1948a, 1948b) (see also Harmer, , 1905Harmer, , 1909. Most recent commentators have implicitly supported this thesis by attributing all pre-Devensian East Anglian tills to this stage West, 1964, 1972;Turner, 1973;Shotton et al, 1977;Perrin et al, 1979;Bowen et al, 1986;Hart and Peglar, 1990;Ehlers et al, 1991;Whiteman, 1995;Bowen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…That this may not necessarily be the case should be borne in mind when assessing the chronology of these features. Solomon (1932) and Baden-Powell and Moir (1942) assigned the sand and gravel of the Blakeney esker to the Wolstonian (or its equivalent) Stage. West (1958), Woodland (1970), Thornton and Cox (in Boulton et al, 1984) and, speculatively, Booth (in Lawson and Allen, 2000 suggested that the landform is of Devensian age, although West (1961) later revised his assessment and proposed that the feature dates from the Wolstonian.…”
Section: Introductionmentioning
confidence: 99%